Two- and three-dimensional lanthanide-based coordination polymers assembled by the synergistic effect of various lanthanide radii and flexibility of a new binicotinate-containing ligand: in situ synthesis, structures, and properties. Issue 3 (8th December 2014) - Ji, Baoming; Deng, Dongsheng; Ma, Junying; Sun, Chaowei; Zhao, Bin
Abstract : The design and synthesis of ten novel coordination polymers was investigated. They have three structural types from 3D to 2D due to the synergistic effect of lanthanide contraction with diverse coordination modes and conformations of the ligand. Abstract : Ten lanthanide coordination polymers have been obtained by the hydrothermal reactions between 3, 3′-dimethoxy-2, 2′-bipyridine-6, 6′-dicarboxylic acid (H2 mbpdc) and rare earth ions, in which H2 mbpdc undergoes an in situ ligand transformation reaction, giving 3, 3′-hydroxy-2, 2′-bipyridine-6, 6′-dicarboxylic acid (hbpdcH4 ). The structures are governed by the synergistic effect of lanthanide contraction with diverse coordination modes and conformations of the ligand. They have three structural types from 3D to 2D polymers. Type I for large ions with the general formula [Ln(hbpdcH)(H2 O)] n (Ln = La III (1 ), Ce III (2 ), Pr III (3 )), possesses a 6-connectedpcu network with unprecedented 2D entangled layers of warp-and-woof threads interwoven by left- and right-handed helical chains; type II for intermediate ions (Ln = Eu III (4 ), Gd III (5 )) and type III for small ions (Ln = Tb III (6 ), Dy III (7 ), Ho III (8 ), Er III (9 ), Lu III (10 )), with general formula [Ln(hbpdcH)(H2 O)2 ] n . The type II and III comprised 2D Ln-hbpdcH grids. A magnetic study of6–8 indicated that the coupling interaction between Ln 3+ ions is weak. In addition, the photophysical properties of Eu and Tb polymers at room temperature were investigated.